Student Perceptions On The Effectiveness Of Using Tophonetics As A Tool For Phonetic Transcriptions - Sirrul Aulia; Fatimah Azzahra; Yani Lubis (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2023)
The goal of this study is to determine the effectiveness of IPA, or phonetic transcriptions, in Tophonetics application based on phonetic transcriptions. Descriptive qualitative research methodologies are employed. Seven students were used as the sample in this study to examine phonetic transcriptions using phonetic tools and gauge participants’ perceptions. In this study, the author employs interviews as a tool to gather data. This study’s conclusion is that students use this tophonetic application to look up phonetic transcriptions. According to the study’s findings, students can readily complete IPA, or phonetic transcriptions in English, using the Tophonetics application rather than utilizing an open dictionary. They can also more easily learn how to utilize the program, which will help them pronounce words more clearly.